Therapists’ lived experience of self-disclosure - Marais, Genevieve; Alistair McBeath (European Journal for Qualitative Research in Psychotherapy, 2021)
The impact and challenges of therapist self-disclosure on the disclosing therapist was explored using Reflexive Thematic Analysis of five interviews with integrative psychotherapists. Three main themes were created: ‘Ambivalent understandings’, ‘Risking rupture and transgression?’ and ‘Regrets, risks and rewards’. Therapist self-disclosure was revealed as a complex and multi-faceted phenomenon which evokes a range of feelings in therapists including regret, anxiety, vulnerability, guilt but also a driving belief that it can enhance client well-being. Therapist self-disclosure is seen as best used sparingly, appropriately, and in alignment with client well-being. A discussion draws out some implications for appropriate clinical practice.